2016
DOI: 10.1039/c5ra23519g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient lipid extraction and quantification of fatty acids from algal biomass using accelerated solvent extraction (ASE)

Abstract: Accelerated solvent extraction optimized for extraction of algal lipids and recovery of polyunsaturated fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The extraction of lipids from the microalgal biomass can be performed using polar organic solvents such as methanol, acetone, and ethanol, as well as low‐polarity organic solvents such as hexane, benzene, toluene, diethyl ether, ethyl acetate, and chloroform. Low‐polarity organic solvents alone are unable to extract NLs effectively as they cannot access those that form strong hydrogen bonds with the polar lipids associated with the cell wall . To access these neutral lipids (NLs), a polar organic solvent must be paired with a low‐polarity organic co‐solvent; the polar organic solvent is intended to disrupt the neutral‐polar lipid complexes and the low‐polarity organic solvent aims to solubilize the intracellular NLs.…”
Section: Lipid Extractionmentioning
confidence: 99%
See 3 more Smart Citations
“…The extraction of lipids from the microalgal biomass can be performed using polar organic solvents such as methanol, acetone, and ethanol, as well as low‐polarity organic solvents such as hexane, benzene, toluene, diethyl ether, ethyl acetate, and chloroform. Low‐polarity organic solvents alone are unable to extract NLs effectively as they cannot access those that form strong hydrogen bonds with the polar lipids associated with the cell wall . To access these neutral lipids (NLs), a polar organic solvent must be paired with a low‐polarity organic co‐solvent; the polar organic solvent is intended to disrupt the neutral‐polar lipid complexes and the low‐polarity organic solvent aims to solubilize the intracellular NLs.…”
Section: Lipid Extractionmentioning
confidence: 99%
“…To access these neutral lipids (NLs), a polar organic solvent must be paired with a low‐polarity organic co‐solvent; the polar organic solvent is intended to disrupt the neutral‐polar lipid complexes and the low‐polarity organic solvent aims to solubilize the intracellular NLs. Solvent systems containing a mixture of low‐polarity and polar organic solvents generally maximize the extraction efficiency of NLs …”
Section: Lipid Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…5−9 It is possible to maximize the extraction of lipids by decomposing polar lipid complexes with polar organic solvents and solubilizing intracellular lipids with nonpolar organic solvents. 7 However, solvent extraction is usually uneconomic due to consumption of much energy to dry the microalgae as pretreatment and the need to separate bio-oil from solvent after extraction. Tsutsumi et al 10 reported that many environmental hazards and safety problems remain in bio-oil recovery by solvent extraction because a large amount of organic solvent is needed.…”
Section: Introductionmentioning
confidence: 99%